If I say if the poems and short stories of Boris Vian - Vian, Boris 1920-1959 (The University of Adelaide Press, 2014)
In two posthumously published collections of short stories, translated for the first time in English in this volume, the France of Jean-Paul Sartre and Simone de Beauvoir is seen through Vian's idiosyncratic and often rather madcap lens. And alongside them there is another voice entirely, a side of Vian that blends his dry irony with deep, at times startling, emotion. His poems, again published in English here for the first time, give a counter-point to the public figure loved throughout France but never quite admitted into the Pantheon of her great artists. For those who may have read L’Écume des jours or J'irai cracher sur vos tombes, or heard someone singing 'Le Déserteur' on the Paris Métro, or for those who are discovering him for the first time, here are both sides of the incomparable and never quite self-coinciding Boris Vian
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Vian, Boris / 1920-1959